Hubungan Daya Ledak Otot Tungkai dan Keseimbangan dengan Accuracy Jump Smash pada Siswa Ekstrakurikuler Badminton - Lolia Manurizal; Made Armade; Masdi Jarniarli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the relationship between leg muscle explosive power and balance with the Accuracy Jump Smash in Badminton Extracurricular Students at SMA Negeri 1 Rambah Hilir. This type of research is correlational and the population in this study amounted to 20 people using the total sampling technique. The leg muscles' explosive power data were collected using the Vertical Jump and Balance Test using the Stork Stand Test, while the Accuracy Jump Smash used the Jump Smash Test to the opponent's area. Data analysis and research hypothesis testing using Product Moment Correlation and Multiple Correlation with a significant level = 0.05. In conclusion, the study (1) there is no significant relationship between Leg Muscle Explosive Power and Accuracy Jump Smash in Badminton Extracurricular Students; (2) there is no significant relationship between Balance and Accuracy Jump Smash in Badminton Extracurricular Students, (3) there is no significant relationship between Limb Muscle Explosive Power and Balance together with Accuracy Jump Smash on Badminton Extracurricular Students. Keywords: Leg Muscle Explosive Power, Balance, Accuracy Jump Smash